Stigmatization of people with mental illness – a matter of milieu-specific worldviews? Results from a population-based survey in Germany - Jenny Spahlholz; Eva Baumann; Sven Speerforck; Sven Speerforck; Christian Sander; Christian Sander; Matthias C. Angermeyer; Georg Schomerus; Georg Schomerus (Frontiers in Psychiatry)
BackgroundDespite numerous awareness campaigns and anti-stigma programs, people with mental illness, particularly schizophrenia, are still stigmatized. Although the society is both cause and solution, societal-level conditions, such as society’s customs and policies that legitimize and perpetuate stigmatization is often neglected. We used a milieu approach to investigate how shared social, cultural and political orientations and expectations are associated with manifestations of the mental-illness related stigma.MethodsWe analyzed cross-sectional data from 3,042 adults aged ≥18 years from a national vignette-based representative survey on the stigma of mental illness in Germany from 2020. For milieu classification, we used an established population segmentation tool based on values and political preferences. Two stigma measures associated with the stereotype and status loss/discrimination components were assessed (i.e., the Social Distance Scale and a list of well-known stereotypes associated with depression or schizophrenia). Descriptive analyses and one-way ANOVAs with post-hoc pairwise contrasts between milieu groups were used to evaluate agreement on stereotypes and the desire for social distance towards people with depression or schizophrenia.ResultsNegative stereotypes about people with a depression (i.e., beliefs about being weak-willed) and schizophrenia (i.e., beliefs about dangerousness) tended to be more common in milieu groups leaning more toward the authoritarian pole. Milieu groups with a more liberal attitude on the socio-cultural dimension further expressed a lower desire for social distance towards people with depression (p<0.001). However, the extent of differentiation between the milieu groups was less pronounced regarding the desire for social distance towards people with schizophrenia than towards people with depression.ConclusionOur findings suggest that socio-cultural and socioeconomic dimensions of the society can be used for both describing heterogeneous societies and illuminating the underlying social structure of stigma. In addition to making blind spots more visible (i.e., schizophrenia), milieu-specific knowledge could be useful in deciding which intervention components are most appropriate for which milieu groups and how to apply them successfully.